Leituras facilitadas como mediação linguística no ensino/aprendizagem de alemão como língua estrangeira1 - Cândido, Abdalan Da Gama; Evangelista, Maria Cristina Reckziegel Guedes [UNESP] (Universidade de São Paulo/Faculdade de Filosofia, Letras e Ciências Humanas/; Programa de Pós-Graduação em Língua e Literatura Alemã, 2020)
While analysing convergences between the use of translation in language teaching and the practice with books known as graded readers (LLFs), we hypothesize that the language facilitation that characterizes these books can be seen as a type of translation, known as linguistic mediation (in German, “Sprachmittlung”). In order to deepen the study of graded readers and considering the interest of German learners in literature in German language, we analysed a graded reader for learners at the B1 level and compared it with the original text. The chosen book was Die Verwandlung [Franz Kafka], adapted by Achim Seiffert (2003). Using computational tools we generated quantitative data related to corpus linguistics, and verified to what extent the lexical profile and structural characteristics of this book contribute to the facilitation of the text. The results show that the analysed graded reader brings learners closer to Kafkas original novel and can contribute to the expansion of their vocabulary, thus characterizing linguistic mediation. Graded readers also enable the reading of classics of literature in German language at intermediate stages of language learning, which would otherwise be difficult or impossible to deal with.

Analisando convergências entre o uso da tradução no ensino de línguas e a prática com livros de leitura facilitada (LLFs), postulamos que a facilitação que constitui esses livros pode ser vista como uma forma de tradução, conhecida por mediação linguística (em alemão, Sprachmittlung). Para aprofundar os estudos sobre os LLFs e considerando o interesse dos aprendizes de alemão como língua estrangeira pela literatura em língua alemã, analisamos uma obra facilitada para nível B1 e a comparamos com o texto original. A obra escolhida foi Die Verwandlung, de Franz Kafka, adaptada por Achim Seiffarth (2003). Utilizando ferramentas computacionais, geramos dados quantitativos ligados à linguística de corpus, buscando verificar em que medida o perfil lexical e as características estruturais dessa obra contribuem para a facilitação do texto. Como resultado, entendemos que o livro de leitura facilitada (LLF) analisado aproxima os aprendizes do texto e pode contribuir para a expansão de seu vocabulário, realizando, portanto, a mediação linguística. Além disso, os LLFs tornam possível a leitura de clássicos da literatura em língua alemã nos estágios intermediários de aprendizagem dessa língua, que de outra forma seria difícil ou impossível.
Graded readers as linguistic mediation in teaching/learning German as a foreign language
Keywords: graded readers; linguistic mediation; German as a foreign language; leitura facilitada; mediação linguística; alemão como língua estrangeira